Four new species of the genus Agrilus Curtis, 1825 from Ecuador (Coleoptera, Buprestidae) - Curletti, Gianfranco (Zootaxa, 2015)
Agrilus delsinnei n. sp., Agrilus yanzatzanus n. sp., Agrilus touroultinus n. sp, Agrilus quito n. sp. from Ecuador are described.